Perceptions of a Healthier Neighborhood Food Environment Linked to Greater Fruit and Vegetable Purchases at Small and Non-Traditional Food Stores. Issue 6 (2nd November 2019) - Barnes, Timothy L.; Lenk, Kathleen; Caspi, Caitlin E.; Erickson, Darin J.; Laska, Melissa N.
ABSTRACT: The aim of this study was to examine associations between perceived neighborhood food environments and food purchasing at small and non-traditional food stores. Intercept interviews of 661 customers were conducted in 105 small and non-traditional food stores. We captured (1) customer perceptions of the neighborhood food environment, (2) associations between customer perceptions and store-level characteristics, and (3) customers' perceptions and shopping behaviors. Findings suggest that customers with more favorable perceptions of the neighborhood food environment were more likely to purchase fruits and vegetables, despite no significant association between perceptions of the neighborhood and objectively measured store characteristics.